The Influence of Financial Literacy and Lifestyle on the Consumptive Behavior : Study On SMK PGRI 7 Students In Malang City - Maida, Nur Al (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the effect of financial literacy and lifestyle on the consumptive behavior of students of SMK PGRI 7 Malang City. The type of research used is quantitative with an associative approach. The research sample amounted to 150 students in grades X, XI, and XII who were selected using proportional random sampling technique. Data were collected through a questionnaire with a Likert scale that had been tested for validity and reliability. The data analysis technique used multiple linear regression with the help of SPSS, as well as the classical assumption test as a prerequisite analysis. The results showed that financial literacy has a significant negative effect on consumptive behavior, while lifestyle has a significant positive effect on consumptive behavior. Simultaneously, financial literacy and lifestyle have a significant effect on students' consumptive behavior. These findings indicate the importance of increasing financial literacy and fostering a simple lifestyle as an effort to reduce consumptive behavior among adolescents